Hubungan antara penglibatan ibu bapa dan motivasi intrinsik murid dengan pencapaian Bahasa Inggeris - Kanniah, Vijaya Nirmalah (2021)
The purpose of this study is to the problem of English language achievement is a common problem faced by primary school students. This situation could be related with the low level of parental involvement and students’ poor motivation intrinsic in the learning process. This study aims to examine the influence of parental involvement and students’ intrinsic motivation towards English achievement among students of SJKT in Kluang district. This study applied quantitative approach whereby the specific design used was correlational study. The respondents involved in this study were 182 students from ten Tamil national type schools in Kluang district. The instruments used were developed based on self -determination Theory, Epstein Theory and Cognitive Development Theory. Data were analyzed descriptively and inferentially using the Spearman rho and multiple regression test.The results of descriptive analysis of parental involvement and intrinsic motivation showed a median of 3.00 which is at a good and positive level.The results of inferential analysis of Spearman rho and multiple regression test showed that there are significant relationship and influence of both variables namely intrinsic motivation and parental involvement towards English achievement. In general, the results of the study showed that parental involvement and intrinsic motivation successfully increased the English language achievement.Therefore, this study implied that parental involvement and students’ motivation intrinsic need to be given attention in students process of learning English.